Atypical acquired hemophilia linked with primary biliary cholangitis: a unique case presentation - Fatma Megdiche; Nour Siala; Faten Kallel; Imen Krichen; Hend Hachicha; Imen Frikha; Maha Charfi; Naourez Kallel; Moez Medhaffar; Hatem Masmoudi; Moez Elloumi; Choumous Kallel (Future Science OA)
Acquired hemophilia A is an uncommon disease often presented with bleeding episodes causing a significant mortality risk. The main responsible for the threatening hemorrhagic disorder is the Factor VIII autoantibody’s development. Acquired inhibitors’ presence is frequently idiopathic, but it can be associated with malignancy, pregnancy, drugs and autoimmune diseases. In this report, we present the first case of acquired hemophilia A associated with primary biliary cholangitis. A 48-year-old man, presented with diffuse oral bleeding after a tooth extraction. Hemostasis testing revealed a markedly prolonged activated partial thromboplastin time. The search for an anti-factor VIII inhibitor returned positive. The etiological investigation concluded primary biliary cholangitis, and the patient was treated with bypassing agent, immunosuppressive therapy, and ursodeoxycholic acid.